Magnetism of Amorphous and Nano-Crystallized Dc-Sputter-Deposited MgO Thin Films - Mahadeva, Sreekanth K. (Nanomaterials (Basel), 2013)
We report a systematic study of room-temperature ferromagnetism (RTFM) in pristine MgO thin films in their amorphous and nano-crystalline states. The as deposited dc-sputtered films of pristine MgO on Si substrates using a metallic Mg target in an O(2) containing working gas atmosphere of (N(2) + O(2)) are found to be X-ray amorphous. All these films obtained with oxygen partial pressure (P(O2)) ~10% to 80% while maintaining the same total pressure of the working gas are found to be ferromagnetic at room temperature. The room temperature saturation magnetization (M(S)) value of 2.68 emu/cm(3) obtained for the MgO film deposited in P(O2) of 10% increases to 9.62 emu/cm(3) for film deposited at P(O2) of 40%. However, the M(S) values decrease steadily for further increase of oxygen partial pressure during deposition. On thermal annealing at temperatures in the range 600 to 800 °C, the films become nanocrystalline and as the crystallite size grows with longer annealing times and higher temperature, M(S) decreases. Our study clearly points out that it is possible to tailor the magnetic properties of thin films of MgO. The room temperature ferromagnetism in MgO films is attributed to the presence of Mg cation vacancies.